Oxygen vacancy stabilized zirconia (OVSZ); a joint experimental and theoretical study - Raza, Mohsin; Cornil, David; Cornil, Jérôme; Lucas, Stéphane; Snyders, Rony; Konstantinidis, Stéphanos (Scripta materialia, 2016)
Understanding the phase formation in zirconia (ZrO2) has triggered a great debate over the last couple of decades, with several mechanisms proposed so far. In the present letter, we demonstrate by well-optimized experimental measurements supported by Density Functional Theory (DFT) calculations that only O vacancies allow for the stabilization of the cubic (c) phase at room temperature. These vacancies distort the zirconia lattice, forcing the crystal to arrange itself in a high symmetric c structure. [Display omitted]